Pigou Meets Ramsey: Gender-Based Taxation with Non-Cooperative Couples - Volker Meier; Helmut Rainer (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2014)
This paper explores the implications of gender-based income taxation in a noncooperative model of household behavior. In a first step, we show how gender-based taxes can act as Pigou taxes and correct the externality induced by a non-cooperative household equilibrium. We find that the first-best Pigou tax rules are solely determined by spouses relative marginal rates of substitution between the public household good and private consumption. Breaking down this eneral rule into the primitives of themodel, the spouse with a comparative advantage in home production should be taxed at a higher rate. In a second step, we embed our non-cooperative framework in a standard second-best planning problem in which taxes serve a revenue-raising purpose. In thiscase, the optimal structure of differential taxation by gender is partly determined by a Ramsey-type inverse elasticity rule and partly by a Pigouvian tax element. We showthat these two forces work in opposite directions in determining whether men or women should be taxed at a higher rate, and that either one could be dominant, depending on the revenue-raising position of the government. This result is robust to the introduction of two groups of households that differ in their mode of decision-making, which can beeither cooperative or non-cooperative.
Keywords: D13; J22; H21; 330; Gender-based taxation; non-cooperative family decision-making